Synthesis of Stilbenes by Cyanide/Base-Mediated Coupling of Benzylic Chlorides and Alcohols - Schichler, Johanna; Madsen, Robert (Synthesis, 2024)
A straightforward procedure has been developed for the direct synthesis of stilbenes from benzylic chlorides and alcohols. The transformation employs a two-step one-pot protocol where the benzylic chloride is first subjected to a substitution with potassium cyanide in o-xylene. Without workup, the resulting arylacetonitrile is then reacted directly with the benzylic alcohol and potassium tert-butoxide to generate the stilbene framework. The condensation has been performed with a variety of commercially available benzylic chlorides and alcohols to afford substituted stilbenes as the pure E-isomers. A kinetic isotope effect of 5.2 has been measured for the overall transformation when comparing benzyl alcohol and α,α-d2-benzyl alcohol. The release of cyanide during the final elimination to stilbene has been confirmed by a picrate test. Thus, the potassium tert-butoxide-mediated elimination of cyanide is believed to proceed by an E1cB mechanism where the deprotonation reaction constitutes the rate-determining step.
Keywords: base-mediated coupling; benzylic alcohols; benzylic chlorides; one-pot reaction; stilbenes